Extrusion-occlusion dynamic failure analysis of O-ring based on floating bush of water hydraulic pump. (January 2020) - Zhang, Zhibin; Wu, Defa; Pang, Hao; Liu, Yinshui; Wei, Wenshu; Li, Ran
Research highlights: Failure causes of O-ring based on floating bush of pump are analyzed. The effect of the alternative change of clearance size is considered. The effect of the abrupt change of fluid pressure is considered. The operating conditions of the O-ring are simulated by finite element analysis. The dynamic equivalent stress and contact stress are obtained. Abstract: The sealing structure of the floating bush is used to connect the cylinder barrel and the valve plate and compensate for the inconsistency of the motion, which is caused by the offset of the cylinder barrel under the external load and the dynamic pressure of the water film. In the process of compensation, the alternative change of clearance size between closing ring and piston bush and the abrupt change of fluid pressure on O-ring make the O-ring extrude and occlude continuously, leading to seal failure and reduced service life. The sealing performance and service life of the O-ring directly affect the working performance of water hydraulic pump. Failure of the O-ring will lead to lower efficiency of water hydraulic pump. In this paper, the geometric relationship of the O-ring is obtained by analyzing the force and motion of cylinder barrel in offset state. Based on Mooney-Rivlin constitutive relation of the rubber material, a two-dimensional finite element model is established. The fluid pressure load and the swing load of the piston bush are applied. The dynamic equivalent stress and contact stress are analyzed, under the limit conditions of the O-ring assembly, loading fluid pressure and swing occlusion. The failure parts and causes are determined, which provides a theoretical basis for the optimization of the sealing structure of the floating bush.